2010
DOI: 10.1002/ckon.201010114
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping – Learning Strategy is Something You Must Learn

Abstract: Concept Mapping Verfahren werden nicht nur zur Wissensdiagnose eingesetzt, sondern zunehmend auch als Lernstrategien im Chemieunterricht. Es handelt sich hierbei um eine anspruchsvolle Strategie, die noch nicht zum Standardrepertoire gehört und deshalb für Lernende eine hohe kognitive Anforderung darstellt. Um die kognitive Belastung beim Inhaltslernen zu reduzieren, ist es sinnvoll, die Strategie zunächst zu üben. Zu diesem Zweck ist ein Trainingsprogramm zum Concept Mapping entwickelt und seine Wirksamkeit ü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In line with other findings Jin and Wong, 2010;Sumfleth et al, 2010), we assume that CMs training and the control training are not sufficient to enable students to construct concept maps. A specific training in the construction of concept maps is needed to improve students' ability to construct concept map as suggested by other authors (e.g., den Elzen-Rump and Leutner, 2007;Sumfleth et al, 2010;Großschedl and Tröbst, 2018).…”
Section: Learning Performance and Concept Map Qualitysupporting
confidence: 81%
See 1 more Smart Citation
“…In line with other findings Jin and Wong, 2010;Sumfleth et al, 2010), we assume that CMs training and the control training are not sufficient to enable students to construct concept maps. A specific training in the construction of concept maps is needed to improve students' ability to construct concept map as suggested by other authors (e.g., den Elzen-Rump and Leutner, 2007;Sumfleth et al, 2010;Großschedl and Tröbst, 2018).…”
Section: Learning Performance and Concept Map Qualitysupporting
confidence: 81%
“…Trainings (i.e., extended periods of practice) increase familiarity and hence support learning effectiveness. It was shown that CM-c trainings improve the ability to construct concept maps (den Elzen-Rump and Leutner, 2007;Jin and Wong, 2010;Sumfleth et al, 2010;Leopold and Leutner, 2015;Becker et al, 2021). In line with this, it was observed that expertise in the use of knowledge maps (Chmielewski and Dansereau, 1998) and concept maps (Chang et al, 2002) improves knowledge structuring and information encoding when summarizing texts.…”
Section: Construction and Study Of Concept Maps -Training Cognitive L...mentioning
confidence: 84%
“…Furthermore, regarding analysis and editing of given concept maps within the error task, the T+ and T− groups performed similar concerning the number of errors detected, but T+ participants corrected these errors considerably more adequately (see Section 3.2). This result implies that the number of detected, and somehow corrected, errors is largely unaffected by the intensity of a CM training, but an extensive CM training can obviously decrease the bias toward correcting errors improperly, which in turn indicates a better understanding of methodical aspects of CM [79,88]. Finally, regarding the number of methodical mistakes made when creating own concept maps both in the learning and in the test phase, participants of the T+ groups clearly outperform those of the T− groups by showing significantly reduced the CM error ratios (see Section 3.5.2).…”
Section: Decision On Hypothesismentioning
confidence: 99%
“…Since CM stimulates the aforementioned processes of organization and elaboration in the course of working on learning material [87], the experimental design of constructing concept maps with simultaneous availability of a learning text (elaboration setting) seems the obvious configuration to enable the learners to understand the text using CM before their learning success is measured [38,71,88].…”
Section: Previous Research On the Effectiveness Of Concept Mapping In Retrieval Settingsmentioning
confidence: 99%